The average rate of change of the function f(x)= the square root of x. From x1=36 to x2=81

Thank you for the opportunity to help you with your question!

we know T = (y2 - y1)/(x2 - x1)

and y1 = f(x1) = sqrt(36) = 6

and y2 = f(x2) = sqrt(81) = 9

so :

T = (9 - 6 ) / (81 - 36 ) = 3/ 45

Good Luck

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up